Is the Brief Multidimensional Student's Life Satisfaction Scale Valid and Reliable for African American Adolescents?. Issue 6 (2nd November 2019) - Valois, Robert F.; Zullig, Keith J.; Brown, Larry K.; Carey, Michael P.; Vanable, Peter A.; Romer, Daniel; DiClemente, Ralph J.
ABSTRACT: Background : Health promotion/education strive to promote healthful conditions that improve quality of life based on the perceptions of those whose lives are affected Though health promotion/education might have instrumental value in reducing risks for premature morbidity and mortality, their ultimate value lies in contributions to quality of life. Life satisfaction (LS) has been defined as an individual's assessment of their quality of life based upon personal criteria and linked to adolescent health risk behaviors and developmental assets. Purpose : We investigated the psychometrics of the Brief Multidimensional Students' Life Satisfaction Scale [BMSLSS] with an adolescent sample of African Americans (N = 1, 658) from four mid-sized cities in the United States. Reliability and validity of the BMSLSS has not been determined for samples of exclusively African American adolescents. Methods : Data analysis included calculating mean ratings, standard deviations and effect sizes (Cohen's d ) and inspecting the scale's internal structure, reliability, and relationships to other variables. Results : Evidence of internal structure, internal consistency reliability, and hypothesized relationships to other variables for participants were determined. Translation to Health Education Practice : The BMSLSS is a useful indicator of LS for research and health education assessment purposes among African American adolescents where brevity of psychometric measures is imperative.